Low pressure spark plasma sintered hydroxyapatite and Bioglass® composite scaffolds for bone tissue repair - Rizwan, Muhammad; Abd Shukor, Mohd Hamdi; Basirun, Wan Jefrey; Kondoh, Katsuyoshi; Umeda, Junko (Elsevier, 2018)
Hydroxyapatite (HA) based composite scaffold materials were prepared by combining it with Bioglass® (BG) to overcome the major limitations of HA such as the lack of osseointegration, inadequate bioactivity and biodegradation. Earlier attempts to prepare BG reinforced HA composites via the conventional sintering process resulted excessive reactions between the constituents and/or crystallization of BG. Excessive reaction between the constituents and crystallization of BG are known to lengthen the bioactivity response. In this work, low pressure spark plasma sintering (SPS) was utilized to prepare HA-BG composite scaffold materials with BG content until 30 wt%. Compared to the conventional sintering practice, the milder processing conditions during the SPS process such as the compaction pressure, sintering time and temperature produced HA-BG composite scaffolds without the excessive reactions between the constituents and prevented the crystallization of BG. All of the developed composites were composed of calcium phosphate (HA and β-Tricalcium Phosphate phases) and glassy phases only. The effect of BG addition on the physical properties such as the bulk density, relative density and hardness are well in line with the XRD and FESEM analyses. The in vitro bioactivity investigation from the immersion of samples in simulated body fluid (SBF) confirmed the improved bioactivity of the composite samples with increased BG content.